Pro PowerShell for Database Developers - Cafferky, Bryan P. (Apress : Imprint: Apress, 2015)
Pro PowerShell for Database Developers helps you master PowerShell application development by continuing where other books leave off. There are no "Hello World" functions here, just real-world examples that get down to business. Develop and deploy database and ETL applications in a reusable framework. Read from any data source and write to any destination. Integrate PowerShell with SQL Server.   Pro PowerShell for Database Developers shows how to dive into the PowerShell environment and customize it to your needs. Learn about function polymorphism using parameter sets, and extend objects via PowerShell-style inheritance. Use PowerShell as an ETL tool surpassing even SSIS. Write full-blown Windows GUI applications, and implement multi-threading through the .NET Windows Workflow Foundation.  All these topics are explained using real-world examples encapsulated into modules you can immediately put to use in your organization. You’ll reap even more as you come to grips with all that PowerShell can do. Begin the journey toward deep expertise and amazing productivity. Buy and read Pro PowerShell for Database Developers today.